ANALISA PENCATATAN PEMOTONGAN IURAN DANA PENSIUN PT. POS INDONESIA CABANG MANADO - Mose, Cynthia Imelda; Elim, Inggriani (Universitas Sam Ratulangi, 2016)
Everyone wants a prosperous life in old age. In the 1970s, people race to sign civil servants because only civil servants who have the assurance of a pension fund. However, in the 1990s after the issuance of Law No. 11 of 1992 on retirement funds, pension funds had not confined to civil servants but also the private sector employees. The purpose of this study was to determine the recording of deducting pension contributions PT. Pos Indonesia Cabang Manado. The analytical method used was descriptive method starts with collecting relevant data with research, analyzes how the recording of deduction contributions to pension funds, and draw conclusions. The results showed that the recording of pension contributions deduction made in accordance with accounting theory and the company only help in collecting and depositing pension contributions to the pension fund account.The company should mantain the recording of pension contribution deduction so the companyâ€™s financial condition could be controlled, especially about pension contribution deduction. Â Keywords: recording, pension fund